Physical association of KAB1 with plant K+ channel alpha subunits. - Tang, H (1996)
K+ channel proteins contain four alpha subunits that align along a central axis perpendicular to membranes and form an ion-conducting pore. Recent work with K+ channels native to animal membranes has shown that at least some members of this protein family also have four beta subunits. These structural components of the holoenzyme each form tight associations with the cytoplasmic portion of an alpha subunit. We have cloned an Arabidopsis cDNA (KAB1) that encodes a polypeptide sharing 49% amino acid identity with animal K+ channel beta subunits. In this study, we provide experimental evidence that the KAB1 polypeptide forms a tight physical association with the Arabidopsis K+ channel alpha subunit, KAT1. An affinity-purified KAB1 fusion protein was immobilized to a support resin and shown to sequester selectively the KAT1 polypeptide. In addition, polyclonal antibodies raised against KAB1 were shown to immunoprecipitate the KAT1 polypeptide as a KAT1-KAB1 protein complex. Immunoblot analysis demonstrated that KAB1 is expressed in Arabidopsis seedings and is present in both membrane and soluble protein fractions. The presence of KAB1 (a soluble polypeptide) in both soluble and membrane protein fractions suggests that a portion of the total amount of native KAB1 is associated with an integral membrane protein, such as KAT1. The presence of KAB1 in crude protein fractions prepared from different Arabidopsis plant organs was evaluated. High levels of KAB1 protein were present in flowers, roots, and leaves. Immunoblot analysis of protein extracts prepared from broad bean leaves indicated that the KAB1 expression level was 80-fold greater in guard cells than in mesophyll cells. Previous studies of the in situ transcription pattern of KAT1 in Arabidopsis indicated that this alpha subunit is abundantly present in leaves and, within the leaf, exclusively present in guard cells. Thus, KAB1 was determined to be expressed in plant organs (leaves) and cell types (guard cells) that are sites of KAT1 expression in the plant. The in situ expression pattern of KAB1 suggests that it may associate with more than one type of K+ channel alpha subunit. Sequence analysis indicates that KAB1 may function in plant K+ channels as an oxidoreductase. It is postulated that beta subunits native to animal K+ channels act as regulatory subunits through pyridine nucleotide-linked reduction of alpha polypeptides. Although the KAB1 primary structure is substantially different from that of animal beta subunits, amino acid motifs critical for this catalytic activity are retained in the plant beta subunit.